Inhibition of lipolysis in Type 2 diabetes normalizes glucose disposal without change in muscle glycogen synthesis rates - Lim, Ee L.; Hollingsworth, Kieren G.; Smith, Fiona E.; Thelwall, Peter E.; Taylor, Roy (Clinical science (1979), 2011)
Suppression of lipolysis by acipimox is known to improve insulin-stimulated glucose disposal, and this is an important phenomenon. The mechanism has been assumed to be an enhancement of glucose storage as glycogen, but no direct measurement has tested this concept or its possible relationship to the reported impairment in insulin-stimulated muscle ATP production. Isoglycaemic–hyperinsulinaemic clamps with [13C]glucose infusion were performed on Type 2 diabetic subjects and matched controls with measurement of glycogen synthesis by 13C MRS (magnetic resonance spectroscopy) of muscle. 31P saturation transfer MRS was used to quantify muscle ATP turnover rates. Glucose disposal rates were restored to near normal in diabetic subjects after acipimox (6.2±0.8 compared with 4.8±0.6 mg·kgffm−1·min−1; P<0.01; control 6.6±0.5 mg·kgffm−1·min−1; where ffm, is fat-free mass). The increment in muscle glycogen concentration was 2-fold higher in controls compared with the diabetic group, and acipimox administration to the diabetic group did not increase this (2.0±0.8 compared with 1.9±1.1 mmol/l; P<0.05; control, 4.0±0.8 mmol/l). ATP turnover rates did not increase during insulin stimulation in any group, but a modest decrease in the diabetes group was prevented by lowering plasma NEFAs (non-esterified fatty acids; 8.4±0.7 compared with 7.1±0.5 μmol·g−1·min−1; P<0.05; controls 8.6±0.8 μmol·g−1·min−1). Suppression of lipolysis increases whole-body glucose uptake with no increase in the rate of glucose storage as glycogen but with increase in whole-body glucose oxidation rate. ATP turnover rate in muscle exhibits no relationship to the acute metabolic effect of insulin.